Autism Characteristics and Behavioural Disturbances in ∼ 500 Children with Down's Syndrome in England and Wales. Issue 4 (24th March 2014) - Warner, Georgina; Moss, Joanna; Smith, Patrick; Howlin, Patricia
<x xml:space="preserve">Abstract</x> Recent research shows that a significant minority of children with Down's syndrome (DS) also meet diagnostic criteria for an autism spectrum disorder (ASD). The present study investigated what proportion of children aged 6–15 years with a confirmed diagnosis of DS in England and Wales display autistic‐type behaviours, and explored the characteristics of this group of children. The Social Communication Questionnaire (SCQ) was used to screen for autism characteristics and the Strengths and Difficulties Questionnaire (SDQ) to explore behavioural difficulties. The proportion of children who met the cut‐off score for ASD on the SCQ (total score ≥ 15) was 37.7% (95% CI: 33.4–42.0%); for autism (total score ≥ 22) the proportion was 16.5% (95% CI: 13.2–19.8%). Children who met the cut‐off for ASD were significantly more likely to be reported as having emotional symptoms, conduct problems and hyperactivity on the SDQ than children who scored well below cut‐off (total score < 10). However, the profile of their autism characteristics on the SCQ was atypical compared with individuals with idiopathic ASD. The pervasiveness of ASD in children with DS in England and Wales is substantially higher than in the general population. These children also experience significantly greater behavioural problems than children with DS only. Early detection of autism characteristics is important for appropriate intervention. However, the unusual profile of autism characteristics in this group may affect the recognition of the disorder and hinder the implementation of appropriate interventions. Autism Res2014, 7: 433–441. © 2014 International Society for Autism Research, Wiley Periodicals, Inc.